PENINGKATAN KOMPETENSI STAF NON-INTERPRETER BALI INTERPRETING DALAM PENGUASAAN BAHASA INGGRIS - I Komang Sulatra; Desak Putu Eka Pratiwi; Ni Luh Seri Wangi (Fakultas Bahasa Asing, 2026)
This community service program was carried out to strengthen the professional capacity of non-interpreter staffs at Bali Interpreting. Based on the fact that many staffs of Bali Interpreting still lacked adequate mastery of English grammar. The program aimed to improve staff competence in using English within real work contexts through structured learning focused on Present, Past, and Future tenses. The implementation method involved needs assessment, interactive teaching, and both formative and summative evaluations. Pre-test results showed that participants had a basic understanding of grammar with an average score of 77.5, but needed further improvement in sentence structure and communication confidence. After the training, the post-test average increased to 87.5, reflecting significant progress in linguistic skills as well as enhanced confidence in speaking and writing. Overall, the program proved effective in addressing the identified needs and contributed to improving the professionalism of Bali Interpreting staffs.